Effect of metformin on the endometrial proteome of diet-induced obese mice - Malliou-Becher, Maria-Nefeli; Turnwald, Eva-Maria; Skupin, Lara; Kretschmer, Tobias; Mesaros, Andrea; Purrio, Martin; Wohlfarth, Maria; Handwerk, Marion; Kalis, Simone; Gründemann, Dirk; Dötsch, Jörg; Germeyer, Ariane; et al. (Journal of molecular endocrinology, 2025)
Obesity is known to have detrimental effects on female fertility, influencing both ovarian and endometrial functions. There is evidence that endometrial function is altered in obese and/or insulin-resistant women. Metformin, an insulin-sensitizing drug, has shown potential in treating metabolic and reproductive disorders, including polycystic ovary syndrome (PCOS) and may enhance fertility outcomes by improving endometrial dysfunction. Using a mouse model, this study aimed to investigate how a high-fat diet impacts endometrial-specific protein expression and whether metformin can mitigate these effects. C57BL/6N mice were fed a standard or high-fat diet and either received metformin treatment or did not. Proteomic analyses revealed significant alterations in endometrial protein expression due to the high-fat diet, while metformin administration appeared to restore many of these changes to normal levels. Metformin’s impact was evident through alterations in specific proteins associated with reproductive health and metabolic functions, such calcium-independent phospholipase A2-gamma, ATP-binding cassette sub-family D member 1, RAC-beta serine/threonine-protein kinase, acyl-CoA:lysophosphatidylglycerol acyltransferase 1, O-GlcNAcase, scavenger receptor class A member 3, protein kinase C beta type, sortilin, beta-2-microglobulin and apolipoprotein C-III. These results suggest a potential therapeutic role for metformin in normalizing endometrial protein expression, providing insights into how this drug could improve fertility outcomes in obese or insulin-resistant females, besides normalizing ovulation patterns. Overall, this study enhances our understanding of the relationship among obesity, endometrial function and metformin’s therapeutic potential, offering a foundation for further research into reproductive health and metabolic disorders.